Accidental Holy Land The Communist Revolution in Northwest China (Edition 1) - Esherick, Joseph W. (University of California Press, 2022)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. Yan'an is China's "revolutionary holy land," the heart of Mao Zedong's Communist movement from 1937 to 1947. Based on thirty years of archival and documentary research and numerous field trips to the region, Joseph W. Esherick's book examines the origins of the Communist revolution in Northwest China, from the political, social, and demographic changes of the Qing dynasty (1644-1911), to the intellectual ferment of the early Republic, the guerrilla movement of the 1930s, and the replacement of the local revolutionary leadership after Mao and the Center arrived in 1935. In Accidental Holy Land, Esherick compels us to consider the Chinese Revolution not as some inevitable peasant response to poverty and oppression, but as the contingent product of local, national, and international events in a constantly changing milieu.